IMPLEMENTATION OF HEAD OF MADRASAH LEADERSHIP IN AN ATTEMPT IMPROVING PROFESSIONALISM TEACHER AT MADRASAH TSANAWIYAH NEGERI TEBING TINGGI CITY - M. Alang Khairun Nizar (International Journal of Educational Research Excellence (IJERE), 2022)
The background of this study is the decline in public interest in the Tebing Tinggi City Public Madrasah Tsanawiyah where the number of student enrollments is only 174 students compared to other public schools which reach more than 200 students in the 2022-2023 school year, so the purpose of this study is to analyze the leadership of madrasa managers. in improving teacher professionalism in terms of decision making, interpersonal communication, exemplary and Funishment and rewards. The research method used is a qualitative approach. The results show that 1) The decision-making process is carried out through discussion and has a positive effect on making improvements to the professional abilities of teachers. 2) The communication between the principal and teachers is formally formed, only in motivating, guiding and reprimanding. This makes a difference in the distance between the teacher and the madrasa head. 3) The Madrasah head provides an example of good behavior such as attendance, punctuality and obedience by following the Madrasah rules and regulations set by the Ministry of Religion. 4) The reward and punishment of the Madrasah Principal is only in the form of praise and reprimand. Awards and punishments were given as words of praise and thanks from the principal and had no effect on motivating MTsN teachers.